Occupational injuries and associated factors among sanitary workers in public hospitals, eastern Ethiopia: A modified Poisson regression model analysis. - Sina Temesgen Tolera; Tesfaye Gobena; Nega Assefa; Abraham Geremew; Elka Toseva (PLoS ONE)
Background Occupational or work-related injuries are mostly common among hospitals' sanitary workers (SWs) in developing countries like Ethiopia. This is due to improper practiced of devices, unhygienic workplace, neglected and undermined risk factors, as well as due to lack of policy initiatives; but not studied well. Objective The aim of the study was to assess the occupational injuries and its associated factors among SWs in public hospitals, eastern Ethiopia: A Modified Poisson regression Model Analysis. Methods An institution-based cross-sectional study was conducted in eight public hospitals in eastern Ethiopia from May 2023 to August 30th, 2023. Out of fourteen hospitals, eight of them were selected randomly. Eight data collectors and 4 supervisors were assigned. Face-to-face interview was conducted. Eight hundred hospital SWs were recruited for the study. Occupational injury was measured using Boolean logic questionnaire either YES [1] or NO [0] for the last 12 months and the 7 days. Descriptive statistical was used for means, medians, standard deviations, and frequencies, proportions, and percentages. Modified Poisson regression was used to explore the relationship of outcome and independent variables. Accordingly, bi-variable analysis was performed to estimate unadjusted prevalence ratio (UPR). While, multi-variable model was used adjusted PR(APR) for those variables have significant values of p ≤0.20 at bi-variate analysis with confidence interval of 95% (CI:95%). Result Out of eight hundred nine SWs, 729(90.1%) were participated on the study. Self-reported occupational injuries among SWs in the last 12 months were 44.0% (95% CI: 40.4, 47.7). Of these, 92.2% (95%CI: 88.7,94.90%) and 7.8% (95%CI: 5.1, 11.3%) occupational injuries was reported from the cleaners and waste collectors, respectively. The model found that SWs those acquired diseases after recruited in the hospitals (APR:1.3;95%CI:1.1,1.6), those had sleeping disorder (APR:1.2;95%CI:1.0,1.), those had workload (APR:1.3; 95%CI:1.0, 1.8), those exposed with occupational hazards (APR:1.4; 95%CI:1.3, 1.7) were at the risk of occupational injuries as compared to their counter parts. Meanwhile, SWs those didn't get supervision (APR: 1.0;95%CI: 1.0, 1.2) and those non-adherence to personal protective equipment (PPE) (APR:1.3;95%CI:1.0,1.5) were more likely to at the risk of occupational injuries. Conclusion The current study concluded that there was a high prevalence of occupational injuries among SWs in the current selected public hospitals. The study also found that non-compliant with PPE, work load, sleeping disorders, attitude towards workplace safety and unsupervised activities and working in high-risk environment tends to increase the risk for occupational injuries. In addition to occupational injuries the study found that SWs those acquired occupational diseases such as asthma, respiratory tract problems, allergy, infections, kidney problems and dermatology problems after recruited in hospitals.